Orthotropic reconstruction and characterization of bone tissues through a visco-plasto-damage model - Gaia Marangon; Riccardo Fincato; Emanuele Luigi Carniel; Ilaria Toniolo; Alice Berardo; Gianluca Mazzucco (PLoS ONE, 2025)
This study presents a robust numerical framework for modeling bone tissue mechanics, integrating an orthotropic visco-plasto-damage model with high-resolution bone geometries derived from computed tomography (CT) scans. The model, implemented within a finite element environment, captures essential bone characteristics, including orthotropic elasticity, viscoplasticity, and progressive damage accumulation. To enhance computational efficiency, an octree-based algorithm has been employed to assign local orthotropic axes based on CT data to enable accurate representation of bone mechanical response across complex geometries. Model calibration, based on experimental data from the literature, supported reliable simulations of cortical and trabecular bone, with validation across a range of loading conditions. The practical efficacy of this approach has been demonstrated through a dental implant case study, wherein stress relaxation, plastic deformation, and damage progression within bone tissue were analyzed. Results indicated a pronounced influence of accurate material orientation on the predicted stress distributions, underscoring the necessity of precise orientation for valid biomechanical simulations. The proposed modeling framework may significantly advance the simulation of bone tissue under realistic physiological conditions, with applications in implant design and evaluation. This method provides a scalable solution for simulating orthotropic materials in biomechanical contexts, combining high-fidelity geometrical reconstruction with a suitable constitutive model, thereby offering a valuable tool for the development and optimization of biomedical implants.